Judge Frank Creede, Jr. Swears In Superior Court Judge Mario Olmos - Watkins, Howard::::::::: (1983)
Daniel Olmos, Mary Louise Frampton holding Margaret Olmos, Judge Mario Olmos by office Christmas tree Law Offices of Olmos and Frampton at 925 N St. #150, Fresno